Image encryption algorithm based on genetic operations and chaotic DNA encoding - Qobbi, Younes; Jarjar, Abdeltif; Essaid, Mohamed; Benazzi, Abdelhamid (Soft computing (Berlin, Germany), 2022)
Based on the two-dimensional logistic map and two genetic operations, a new image encryption algorithm is suggested. Encrypted image is constructed in two phases: confusion and genetic operations. In the first phase, the confusion is used to overcome the problem of uniform images. In the second phase, the image is encoded into DNA (deoxyribonucleic acid) sequences; then, the genetic operations are performed including crossover and mutation after decomposition the image into blocks of 12 nucleotides (adenine (A), guanine (G), cytosine (C) and thymine (T)). A cipher block chaining (CBC) mode based on genetic operations is used to ensure the security of our algorithm from any differential attack. Simulations performed on large number of images of different size ensure that our method is not subject to any known attacks.